In-Situ Polymerization for Catalytic Graphitization of Boronated PAN Using Aluminum and Zirconium Containing Co-Catalysts - Taewoo Kim; Byoung-Suhk Kim; Tae Hoon Ko; Hak Yong Kim (Inorganics)
In-situ polymerization is an effective method for integrating co-catalysts homogeneously into the polymer matrix. Polyacrylonitrile (PAN)-derived highly graphitized carbon is a state-of-the-art material with diverse applications, including materials for energy storage devices, electrocatalysis, sensing, adsorption, and making structural composites of various technologies. Such highly graphitized materials can be effectively obtained through in-situ polymerization. The addition of external catalysts during in-situ polymerization not only enhances the polymerization rate but also facilitates the degree of graphitization and quality of graphitic carbon upon graphitization at moderate temperatures. In this study, we apply an in-situ polymerization technique to integrate aluminum triflate (Al(OTf)3) and zirconocene dichloride (C5H5)2ZrCl2 co-catalyst into a boronated polyacrylonitrile (B-PAN) matrix. The in-situ polymerization ensures the uniform distribution of the co-catalyst without aggregation, facilitating the formation of a well-ordered graphitic structure at a moderated temperature. Boronated polyacrylonitrile (B-PAN) solutions, with and without co-catalyst (Al(OTf)3, (C5H5)2ZrCl2 or both) were prepared through polymerization process, dried in an oven, and then subjected to graphitization at 1250 °C with a heating rate of 1 °C min−1 for 1 h under an N2 atmosphere. The resulting graphitic carbon was characterized to determine the impact of co-catalyst on the degree of graphitization. This study provides valuable insights into synthesizing high-quality graphitic carbon materials, offering promising pathways for their scalable production through the strategic use of in-situ polymerization and co-catalysis. These materials have potential applications in various fields, including environmental technologies, energy storage, and conversion, offering a pathway to design facile and economical graphitic carbon materials.